A case of skin necrosis as a result of cholesterol crystal embolisation - (:unkn) unknown (ELSEVIER SCI LTD, 2006)
Cholesterol crystal embolism is a multisystem disorder with a high mortality. It is usually seen following vascular surgery and long term anticoagulation therapy, but the diagnosis is often not considered. Skin manifestations are the first sign of cholesterol crystal embolism and recognition of the symptoms is a key element in early diagnosis and prevention of recurrences. We report a case who presented with acute renal failure, livedo reticularis and skin necrosis following angioplasty. Cutaneous biopsy revealed cholesterol crystals in the lumen of a vessel. Necrotic sites were treated with daily wound care and he was operated for reconstruction of tissue defects with cutaneous advancement flaps. One month after the operation heating was complete. (C) 2005 The British Association of Plastic Surgeons. Published by Elsevier Ltd. All. rights reserved.
Keywords: cholesterol crystal embolism; chotesterol embolism; cholesterol embolization syndrome; livedo reticularis; LIVEDO-RETICULARIS; CUTANEOUS MANIFESTATIONS; CARDIAC-CATHETERIZATION; RENAL-DISEASE; RISK-FACTORS; EMBOLISM; COMPLICATION; DIAGNOSIS